Certainty of Legal Protection for Justice Collaborators in Indonesia - Nurhayani, Nurhayani; Bardi, Ahmad (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The justice collaborator system is a new system in criminal procedural law in Indonesia. The legal basis for justice collaborators is currently still regulated in Law No. Law of the Republic of Indonesia No. 31 of 2014 concerning amendments to Law of the Republic of Indonesia No. 13 of 2006 concerning Protection of Witnesses and Victims. The issues being analyzed are legal certainty and forms of legal protection. to justice collaborators. The research method used is normative legal research with statutory and conceptual approaches. The results of the study show that the legal sources of Justice collaborators are currently not regulated in the Criminal Procedure Code, but are still regulated in one law with reporting witnesses and victim witnesses. The form of protection given to perpetrator witnesses (justice collaborators) who have status as suspects or defendants is protection for personal security, family and property, free from threats, giving statements without pressure, getting translators, free from ensnaring questions, getting information about progress of the case, obtain information regarding court decisions, obtain information in terms of the convict being released, keep his identity confidential, obtain a new identity, obtain temporary residence, obtain a new residence, obtain reimbursement of transportation costs as needed, obtain legal advice, obtain temporary living expenses assistance until the Protection deadline expires; and/or receive assistance. Meanwhile, justice collaborators whose status as convicts are conditional release, additional remissions and the rights of other convicts.